Designing Discoverable Digital Tabletop Menus for Public Settings - Seto, Amanda Mindy (University of Waterloo, 2012)
Ease of use with digital tabletops in public settings is contingent on how well the system invites and guides interaction. The same can be said for the interface design and individual graphical user interface elements of these systems. One such interface element is menus. Prior to a menu being used however, it must first be discovered within the interface. Existing research pertaining to digital tabletop menu design does not address this issue of discovering or opening a menu. This thesis investigates how the interface and interaction of digital tabletops can be designed to encourage menu discoverability in the context of public settings. A set of menu invocation designs varying on the invocation element and use of animation are proposed. These designs are then evaluated through an observational study at a museum to observe users interactions in a realistic public setting. Findings from this study propose the use of discernible and recognizable interface elements – buttons – supported by the use of animation to attract and guide users as a discoverable menu invocation design. Additionally, findings posit that when engaging with a public digital tabletop display, users transition through exploration and discovery states before becoming competent with the system. Finally, insights from this study point to a set of design recommendations for improving menu discoverability.
Keywords: Digital Tabletops; Interface Design; System Design Engineering